A Co(ii) framework derived from a tris(4-(triazol-1-yl)phenyl)amine redox-active linker: an electrochemical and magnetic study. Issue 28 (28th June 2018) - Ngue, Chin-May; Chiu, Ching-Wen; Lee, Gene-Hsiang; Peng, Shie-Ming; Leung, Man-Kit; Yang, Chen-I.; Liu, Yen-Hsiang; Lu, Kuang-Lieh
Abstract : This is a rare case of a solid-state electrochemical and spectroelectrochemical study of coordination polymers. Furthermore, the framework exhibits an interesting field-induced magnetic spin-flop transition. Abstract : A new 3D coordination polymer [Co2 (μ-OH2 )(TTPA)(DTDN)2 ·DMF]·H2 O n (1, TTPA = tris(4-(1 H -1, 2, 4-triazol-1-yl)phenyl)amine, DTDN = 6, 6′-dithiodinicotinate) was synthesised and characterised. The redox properties of this framework were elucidated by solid state electrochemical and spectroelectrochemical data. This is the first investigation of the redox behaviour of TTPA in coordination polymers. Furthermore, the incorporation of a paramagnetic Co(ii ) metal ion into the framework caused1 to show spin-flop behaviour as the result of a field-induced magnetic transition. The incorporation of two flexible ligands and Co(ii ) metal ions represents a feasible approach for the advancement of multifunctional materials.